A case report of a completely displaced stress fracture of the femoral shaft in a middle-aged male athlete – A precursor of things to come?. (May 2016) - Larsen, Peter; Elsoe, Rasmus; Rathleff, Michael S.
Abstract: Background: Displaced stress fractures of the femoral shaft are very uncommon. The proportion of middle-aged and older age groups participating in long-distance running, triathlon and other high intensity sports is increasing. As a consequence stress fracture of the femoral shaft may be on the rise in the future. Case presentation: The patient was 43 years old male caucasian triathlete. The authors met the patient after he was admitted with a displaced femoral shaft fracture. The fracture occurred during running at the national championship in ½ Ironman. The patient reported that his symptoms had gradually developed over the last month before the fracture with pain localized anterior to the thigh. The patient interpreted the symptoms as local muscle damage. A clinical examination was conducted by a physiotherapist and the symptoms were interpreted as a simple muscle injury in the quadriceps. Conclusion: When presented with a patient with non-traumatic, diffuse anterior thigh pain in an individual of this age, who is participating in high-level endurance running; clinicians should consider the possibility that the cause of the symptoms may be a femoral shaft stress fracture.